Obesity: Friend or Foe in Sjögren’s Syndrome Patients? - Kincső Mezei; Laura Nagy; Viktória Orosz; Zsófia Aradi; Bernadett Bói; Antónia Szántó (Diagnostics)
Background/Objectives: In Sjögren’s syndrome, exocrine glands are destructed in an autoimmune-mediated process. Obesity is known to influence a wide range of diseases. This study aimed to examine whether obesity has an impact on the disease course of our patients with Sjögren’s syndrome. Methods: Out of the regularly followed-up patients, 125 were grouped based on their body mass index (BMI). Below a BMI of 25, they were listed as “non-obese” (n = 45), whereas above a BMI of 25, they were categorized as “obese” (n = 80). Demographic, laboratory, and immunological parameters; Sjögren’s syndrome disease activity index; certain extraglandular manifestations; and treatment modalities were compared using biostatistical methods. Results: Among the examined cardiovascular and cerebrovascular co-morbidities, type 2 diabetes and hypertension were significantly more frequent in the obese group. Considering the associated further autoimmune disorders and extraglandular manifestations, in our patients, there were no significant differences between the two groups. Among laboratory parameters, gamma glutamil transferase, alanine transaminase, hemoglobin, hematocrit, lymphocyte rate, triglyceride, and c3 and c4 complement levels were significantly higher in the obese group, while the proportion of rheumatoid factor positivity and the neutrophil granulocyte rate were significantly lower. Immunoglobulin G, A, and M levels did not differ significantly between the two subsets. Obese patients needed steroid therapy significantly less frequently; however, statin therapy was remarkably more frequent in that group. Furthermore, the European League Against Rheumatism (EULAR) Sjögren’s syndrome disease activity index (ESSDAI) was significantly lower in the group of overweight patients. Conclusions: Our results suggest that several immunological parameters of obese patients are more favorable compared to those with normal body weight. Behind that, we might suspect either the beneficial effect of statin therapy and/or the obesity paradox.